INTERAKSI ANTAR AKTOR DALAM PENGELOLAAN PARKIR DI KAWASAN PANTAI MATAHARI TERBIT - Sipahutar, Wulan Agnesia; -, Bandiyah; Jayanthi Mertha, Anak Agung Sagung Mirah Mahaswari (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
This study analyzed the problem of how is the interaction between actors in the Sunrise Beach park, by looking at the pattern of each interaction, namely First, the interaction between Sanur Village and Sanur Bersatu. The second is the interaction of Sanur Village with Denpasar Parking Company. Third, Sanur Village with Denpasar Parking Company and Private Company (Skyline). The study uses State in Society theory and Political Economy theory. This research used a descriptive qualitative method by using primary and secondary data. This research shows that the relationship between Denpasar Parking Company, Skyline and Sanur Village is based on the principle of interdependence and mutual need. The involvement of various actors is a fairly good implementation of political economic policies in Sanur area, where always considering the harmony of power and social living in the community, so that the parties involved are quite advantaged in the sustainability of parking management . Keywords: Interaction of Actors, Parking Management, State in society, Sunrise Beac h.